2008
DOI: 10.1890/07-1559.1
|View full text |Cite
|
Sign up to set email alerts
|

Woody Plants in Grasslands: Post‐encroachment Stand Dynamics

Abstract: Woody plant abundance is widely recognized to have increased in savannas and grasslands worldwide. The lack of information on the rates, dynamics, and extent of increases in shrub abundance is a major source of uncertainty in assessing how this vegetation change has influenced biogeochemical cycles. Projecting future consequences of woody cover change on ecosystem function will require knowledge of where shrub cover in present-day stands lies relative to the realizable maximum for a given soil type within a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
135
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(142 citation statements)
references
References 58 publications
4
135
2
1
Order By: Relevance
“…Previous studies on temporal patterns of shrub colonization have mostly focused on the role of site conditions (Browning et al, 2008;Davies et al, 2010;Levick and Rogers, 2011), fire (Malkisnon et al, 2011) and grazing (Roques et al, 2001). We observed that aspect and rock cover were significant predictors of shrub patch density.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Previous studies on temporal patterns of shrub colonization have mostly focused on the role of site conditions (Browning et al, 2008;Davies et al, 2010;Levick and Rogers, 2011), fire (Malkisnon et al, 2011) and grazing (Roques et al, 2001). We observed that aspect and rock cover were significant predictors of shrub patch density.…”
Section: Discussionmentioning
confidence: 53%
“…Visual interpretation of generated images was performed to mark the presence of patches. Our sample unit was a shrub patch, defined as a woody plant Browning et al, 2008). In each texture layer, the same author (VR) marked the location of each shrub patch within the EU, to minimize observer bias.…”
Section: Aerial Photography Interpretationmentioning
confidence: 99%
See 3 more Smart Citations